Differential Role of Adipose Tissues in Obesity and Related Metabolic and Vascular Complications - Almudena Gómez-Hernández; Nuria Beneit; Sabela Díaz-Castroverde; Óscar Escribano (International Journal of Endocrinology)
This review focuses on the contribution of white, brown, and perivascular adipose tissues to the pathophysiology of obesity and its associated metabolic and vascular complications. Weight gain in obesity generates excess of fat, usually visceral fat, and activates the inflammatory response in the adipocytes and then in other tissues such as liver. Therefore, low systemic inflammation responsible for insulin resistance contributes to atherosclerotic process. Furthermore, an inverse relationship between body mass index and brown adipose tissue activity has been described. For these reasons, in recent years, in order to combat obesity and its related complications, as a complement to conventional treatments, a new insight is focusing on the role of the thermogenic function of brown and perivascular adipose tissues as a promising therapy in humans. These lines of knowledge are focused on the design of new drugs, or other approaches, in order to increase the mass and/or activity of brown adipose tissue or the browning process of beige cells from white adipose tissue. These new treatments may contribute not only to reduce obesity but also to prevent highly prevalent complications such as type 2 diabetes and other vascular alterations, such as hypertension or atherosclerosis.